Violation of Medical Oath as a Criminal Office of Health Law - Nadia Nabela; Joko Setiyono (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
As rights protected by the constitution, the right to health services is highly demanded by the government. On this basis, the state is obliged to respect, protect, and fulfill these rights, including by providing equal access to health services, preventing actions that can reduce the level of public health. In the 2012 Code of Medical Ethics, the violation of the medical oath is a violation of the Code of Ethics. However, in this paper the author examines more from the criminal side. Can a violation of an oath be considered a criminal offence? Therefore, this study examines Medical Discipline Violations as Violations of Criminal Law. The method that the author uses in this research is a normative legal approach method using secondary data sources which include primary legal materials, secondary legal materials and tertiary legal materials.The results of the research in this paper are: the author concludes that the violation of the medical oath is a form of action that is medical error (malpractice). When viewed from the form of medical ethics violations, it is a violation of the Standard Operating Procedures and Professional Standards and the rules/provisions for the application of science in the implementation of other medical practices. Then it is to be able to prove the error through a medical audit in determining the position of the error (malpractice).